Torsion of the greater omentum: A rare preoperative diagnosis - Ankit Anil Tandon; Kian Soon Lim (Indian Journal of Radiology and Imaging, 2010)
Torsion of the greater omentum is a rare acute abdominal condition that is seldom diagnosed preoperatively. We report the characteristic computed tomography (CT) scan findings and the clinical implications of this unusual diagnosis in a 41-year-old man, who also had longstanding right inguinal hernia. Awareness of omental torsion as a differential diagnosis in the acute abdomen setting is necessary for correct patient management.